266 Tumour mutation burden (TMB) and efficacy outcomes in the phase III DANUBE study of advanced urothelial carcinoma (UC). (10th December 2020) - Wildsmith, Sophie; Walker, Jill; L'Hernault, Anne; Li, Weimin; Bye, Hannah; He, Philip; Xiao, Feng; Zhang, Qu; Stewart, Ross; Reyes, Melissa de los; Raja, Rajiv; Levin, Wendy; et al.
Abstract : Background: The phase III DANUBE study assessed the efficacy of the PD-L1 inhibitor durvalumab (D), alone or in combination with the CTLA-4 inhibitor tremelimumab (T), versus standard of care chemotherapy (SoC) for the first-line treatment of unresectable, locally advanced or metastatic UC. The study did not meet its co-primary endpoints of improving overall survival (OS) for D monotherapy vs SoC in patients with high tumor PD-L1 expression or for D+T vs SoC in the intention-to-treat population. 1 TMB measurement in blood (bTMB) or tumour (tTMB) has been linked to improved efficacy with PD-1/PD-L1 inhibitors in UC and with D+T in non-small cell lung cancer, 2 thus providing a rationale to explore TMB in the DANUBE trial. Methods: Baseline plasma samples from DANUBE were assessed for bTMB using the Guardant OMNI platform, while baseline tTMB was measured in formalin-fixed paraffin-embedded (FFPE) tumour samples using the FoundationOne CDx gene panel. Associations between progression-free survival (PFS) and median and landmark OS with bTMB and tTMB levels at various cutoffs were assessed as part of a pre-specified exploratory analysis. The data cutoff occurred on January 27, 2020. Results: Among 1032 patients randomised in DANUBE, 536 (51.9%) were evaluable for bTMB and 623 (60.4%) were evaluable for tTMB. For D vs SoC, bTMB and tTMB were not associated with OS or PFS at any cutoff. For D+T, stronger associations between bTMB and OS as well as PFS were observed with increasing bTMB cutoffs (table 1 ). At the bTMB cutoff ≥ 24 mut/Mb, 12-month OS rates were 76.7% for D+T and 54.3% for SoC, whereas for bTMB < 24 mut/Mb, 12-month OS rates were 53.4% for D+T and 51.2% for SoC. Similar trends for both OS and PFS were observed with tTMB (table 1 ). Conclusions: Both bTMB and tTMB are potentially useful biomarkers for enriching responses to D+T in previously untreated, advanced UC. Neither bTMB nor tTMB was associated with better outcomes for D monotherapy. Cutoffs of 24 mut/Mb for bTMB and 10 mut/Mb for tTMB appear optimal for D+T in the setting of previously untreated, advanced UC. Trial Registration: The trial is registered with ClinicalTrials.gov, NCT02516241, and the EU Clinical Trials Register, EudraCT number 2015-001633-24. References: AstraZeneca. Update on phase III DANUBE trial for IMFINZI and tremelimumab in unresectable, stage IV bladder cancer [press release] March 6, 2020. [https://www.astrazeneca.com/media-centre/press-releases/2020/update-on-phase-iii-danube-trial-for-imfinzi-and-tremelimumab-in-unresectable-stage-iv-bladder-cancer-06032020.html] Rizvi NA, Cho BC, Reinmuth N, et al. Durvalumab with or without tremelimumab vs standard chemotherapy in first-line treatment of metastatic non-small cell lung cancer: The MYSTIC phase 3 randomized clinical trial. JAMA Oncol. 2020 :6:661–674. Ethics Approval: The study protocol was approved by the Ethics Board at each investigator's institution.